Multiscale spatial organization of RNA polymerase in Escherichia coli. - Endesfelder, U; Finan, K; Holden, S; Cook, P; Kapanidis, A; Heilemann, M (2013)
Nucleic acid synthesis is spatially organized in many organisms. In bacteria, however, the spatial distribution of transcription remains obscure, owing largely to the diffraction limit of conventional light microscopy (200-300 nm). Here, we use photoactivated localization microscopy to localize individual molecules of RNA polymerase (RNAP) in Escherichia coli with a spatial resolution of ∼40 nm. In cells growing rapidly in nutrient-rich media, we find that RNAP is organized in 2-8 bands. The band number scaled directly with cell size (and so with the chromosome number), and bands often contained clusters of >70 tightly packed RNAPs (possibly engaged on one long ribosomal RNA operon of 6000 bp) and clusters of such clusters (perhaps reflecting a structure like the eukaryotic nucleolus where many different ribosomal RNA operons are transcribed). In nutrient-poor media, RNAPs were located in only 1-2 bands; within these bands, a disproportionate number of RNAPs were found in clusters containing ∼20-50 RNAPs. Apart from their importance for bacterial transcription, our studies pave the way for molecular-level analysis of several cellular processes at the nanometer scale.